The language of folding: increasing spatial language and decreasing mathematics anxiety through origami - Ridgley, Lisa M.; Geary, David C.; Li, Yaoran; Myers, Perla; Ottinger, Rebecca; Silvaggio, Danielle N.; Ünal, Zehra; Popov, Vitaliy (Frontiers in Education, 2025)
Although crucial for mathematical problem solving and long-term STEM achievement, visuospatial skills remain a significant challenge for many students in the United States. Therefore, it is critical to explore how spatial skill interventions can be integrated into mathematics curriculum. This research examines the effects of Project VisMO, a hands-on, origami-based curriculum and after-school program, on elementary school children's visuospatial skills, mathematical competencies, and mathematics anxiety and attitudes. An initial randomized control trial (RCT) of the online VisMO program, conducted during the COVID-19 pandemic with 179 elementary students, demonstrated promising results in enhancing spatial vocabulary and reducing mathematics anxiety. Two follow up studies of the VisMO program were conducted, featuring a 5-week and a 12-week intervention. Both studies confirmed improvements in spatial vocabulary, a reduction in math anxiety, and potential geometry gains. We discuss the need for further research on the in-person program and the importance of designing structured professional development for educators to enhance their self-efficacy and knowledge of incorporating visuospatial interventions into their teaching.